Indigenous knowledge and globalisation in Bangladesh: NGOs’ capacity for social capital and community development - Islam, Md. Rezaul (2009)
The thesis reflects on contemporary community development in Bangladesh within the context of competing streams of indigenous and global knowledge. It examines Bangladeshi non-government organisations (NGOs) and their capacities for social capital and community empowerment, with the view that a ‘new knowledge approach’ is needed to achieve ‘sustainable community development’. The framework is informed by qualitative research, and a number of qualitative data collection methods were employed, which aided a triangulation of perspectives. The research focuses on two communities (one urban, the other rural) from two NGOs in Bangladesh: Proshika and Practical Action Bangladesh (PAB). Data was obtained from two indigenous occupations: blacksmiths and goldsmiths. It initially transpired that there were problems within these communities, where NGOs’ capacities for social capital and community development were limited. It is suggested that a new approach to knowledge is needed, which considers community development as not simply economic development, but as a social sphere with its own way of thinking. This has several implications for the contributions of NGOs. This is in terms of the new knowledge being approached through the metaphor of the ‘middle ground’, which acts as a device to help conceptualise ‘a field of action’ between community life and policy processes. This provides a basis from which to take a critical view of concepts, such as social capital and community empowerment, in the context of globalisation. The thesis argues for the need to find a point of conjuncture between indigenous and global knowledge based development approaches in order to develop new theoretical coherence within development studies and community development theory.